Postgraduate students’ access and use of digital information resources and services for research in university libraries in Kaduna State - Jibrin, Adamu; Mohammed, Zakari; Umar, Lawal; Maifata, Nurudeen Mu’azu (Communicate: Journal of Library and Information Science, 2025)
This study was carried out to investigate the Postgraduate Students’ Access and Use of Digital Information Resources and Services for Research in University Libraries in Kaduna State. In order to achieve this, two research questions and one null hypothesis were formulated and tested to guide the study. These include: the types of digital information resources and services accessed and used for research by postgraduate students in the university libraries in Kaduna State, Nigeria and the extent of which Postgraduate Students access and use digital information resources and services for research in the University Libraries studied. Survey research method was adopted for the study. The population of the study consisted of 18,130 postgraduate students from the 3 universities namely; Kashim Ibrahim Library (KIL) of Ahmadu University, Zaria, Kaduna State University (KASU) Library and Nigerian Defence Academy (NDA) Library and 377 of them were drawn as the sample size of the study. It was discovered that that audio visual and communication services, emailing services, printing services, public access catalogue, customer care services, online information search services, and digital document delivery services were the digital information services highly accessible and used by the postgraduate students studied. Also, there is no significant relationship between access and use of digital information resources and services by postgraduate students in the university libraries in Kaduna State. It is recommended that University management in collaboration with university librarian should expand subscription to more online database in order to promote postgraduate students’ access and use of digital information resources and services for their research activities.